Analysis of the Relationship between Work Attitudes and Work Motivation on Employee Work Productivity at CV Iswara - Nafilatul Fitri; Fresvian Jenrivo; Rizki Mustika Riswari; Komang Aditya Surya Negara (Universitas Muhammadiyah Malang, 2024)
Productivity is important in a company, because if the level of productivity is high, it will produce products that meet or exceed the desired target. Programs related to motivation and work attitudes can help support company facilities. With a good work motivation program for improving human resources, human resources can be improved for the better. With this, it can support the vision and mission of a company, one of which is achieving production targets thereby increasing company funds. The aim of this research is to determine the relationship between work attitudes and productivity, the relationship between work motivation and productivity, and determine work productivity. The research method used is quantitative with techniques total sampling on 35 employees using multiple linear regression analysis, with questionnaire instruments, and the SPSS method. Based on the analysis, results were obtained from the relationship between work attitude and productivity, motivation and productivity, and work productivity, with the majority of workers having good levels of work attitude, work motivation, and work productivity. Based on the statistical output, the significance value of the relationship between attitudes and productivity has a p value = 0.001b (sig < 0.05). The relationship between motivation and productivity has a p value = 0.001b (sig < 0.05). Work attitude and work motivation have a significant relationship with work productivity.